Anticentromere antibody-positive primary Sjögren's syndrome: Epitope analysis of a subset of anticentromere antibody-positive patients. Issue 1 (2nd January 2017) - Tanaka, Noriyo; Muro, Yoshinao; Suzuki, Yasunori; Nishiyama, Susumu; Takada, Kunio; Sekiguchi, Masahiro; Hashimoto, Naoaki; Ohmura, Koichiro; Shimoyama, Kumiko; Saito, Ichiro; Kawano, Mitsuhiro; Akiyama, Masashi
Abstract : Objectives : Anticentromere antibody (ACA) is generally considered to be a serological marker for systemic sclerosis (SSc). ACA-positive patients with primary Sjögren's syndrome (pSS) have also been reported. ACA often recognizes centromere proteins (CENPs): CENP-A, CENP-B, and CENP-C, and sometimes reacts to heterochromatin protein 1 (HP1)α. We compared the reactivity against six different epitopes for three ACA-positive clinical subgroups: 29 patients with pSS, 36 SSc patients with sicca symptoms, and 28 SSc patients without sicca symptoms. Methods : We utilized enzyme-linked immunosorbent assays (ELISAs) with recombinant proteins covering six different epitope regions of ACA (the amino terminus (Nt) of CENP-A, CENP-B, and CENP-C, the carboxyl terminus (Ct) of CENP-B and CENP-C, and HP1α). Results : The patients with pSS were found to have IgG-class autoantibodies against CENP-C-Nt and HP1α, and IgA-class autoantibodies against CENP-C-Ct with significantly higher frequencies than the SSc patients with or without sicca symptoms. The positive predictive value and the negative predictive value of the combination of these three autoantibodies for pSS were 73% and 82%, respectively, for pSS. Conclusions : Based on the result that reactivities against CENP-C and HP1α in patients with pSS differ from those in patients with SSc, we propose ACA-positive pSS as a clinical subset of SS that is independent of SSc.